Effectiveness of Ginger Aromatherapy on Blood Pressure Among Hypertensive Patients in a Community Health Center in Indonesia: A Quasi-Experimental Study - Long, Andre Liang; Marlina, Th. Titin; Rina S, Fransisca Anjar (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Hypertension is a disease caused by several factors including genetic factors, physical changes, unhealthy lifestyles, the presence of certain medical conditions. One way to manage hypertension in a non-pharmacological way is using aromatherapy. Objective: This research was conducted to determine the effect of ginger aromatherapy on blood pressure in hypertensive patients at the Ngemplak II Health Center, Sleman Regency. Methods: The research design used was quasy experimental design with a non-equivalent control pre-posttest design approach. The study population was all hypertensive patients who conducted examinations at the Ngemplak II Health Center, Sleman Regency. The number of samples in this study were 50 respondents who were divided into 2 groups, namely 25 intervention groups and 25 control groups taken by purposive sampling technique. The intervention group was given ginger aromatherapy with a duration of 30 minutes per day for 3 days using a diffuser, while the control group only measured blood pressure on the first day and the third day. Results: The results showed that a small proportion of hypertensive patients were elderly (38%), mostly female (64%), and mostly worked as farmers (52%). Data analysed using the Mann-Whitney test showed that there was a significant difference in mean systolic blood pressure between the intervention and control groups (p value <0.001), however, between the intervention group and the control group, there is no significant difference in diastolic blood pressure(p = 0.460). Conclusion: Ginger aromatherapy has been proven effective as a non-pharmacological therapy for controlling blood pressure in hypertensive patients. Further research with a more accurate design and stricter control of confounding factors is recommended to follow up on the results of this study